Husband's Knowledge and Employment Status Related with Exclusive Breastfeeding - Mardiah Mardiah; Budi Astyandini; Rafika Fajrin (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2023)
Exclusive breastfeeding for baby’s aged 0-6 months nationwide is only 71.58%. The percentage of exclusive breastfeeding in East Sumba Regency was 77.8%, while the percentage of exclusive breastfeeding for baby’s aged 0-6 months in Tanaraing Health Center was 64.6%. The purpose of this study was to determine the effect of knowledge level and husband's employment status on exclusive breastfeeding in Tanaraing Health Center. This research method is quantitative using correlation analysis. The results of this study showed that there was a relationship between knowledge level and employment status of husbands on exclusive breastfeeding with significant knowledge of 0.000 (<0.05) using Chi Square test and employment status of 0.023 (<0.05) using Fisher Exact test. In addition, knowledge and employment status also showed a significant influence using the t-test. It was concluded that most of the husbands' knowledge was lacking, most of the husbands' employment status was as laborers, so the level of education and employment status both have an influence on exclusive breastfeeding. However, employment status has more influence on exclusive breastfeeding with a significance value of 0.000 and a t-value of 4.675. Suggestions to the Tanaraing Health Center to continue to do more health promotion and education, especially on exclusive breastfeeding, targeting not only mothers but also husbands and families.